Characterization of patients operated on for hip fracture - José Luis Nápoles Mengana; Osmar Rodríguez Obret; Jaime Humberto González Tuero; Angelina Mourlot Ruíz; Gipsy Martínez Arzola (Revista Cubana de Medicina Militar)
Introduction: Hip fracture is a serious health problem; it is the one with the highest mortality and decreases life expectancy by almost two years. Objective: To determine the clinical-epidemiological characteristics of patients with hip fractures. Method: An observational, descriptive study was carried out in 69 patients operated on for hip fracture. Sex, age, hip fracture production mechanism, type of fracture, preoperative evolution, surgical technique, complications, postoperative stay and discharge status were analyzed. Results: The most affected age group was 80 and over, with 37 % of the total. There was a predominance of the female sex for 68,1 %. The fall from his own feet predominated for 76, 8 %. The surgical method of angled blades of 130 0, of the AO system, is the most used for 60,9 %, as well as the surgical intervention was performed in the first 24 hours for 76,8 %. Conclusions: Hip fracture predominates in patients of the eighth decade of life, mainly female. The most commonly observed varieties of fractures are the extracapsular ones. Osteosynthesis with a 130º angled blade is the most widely used surgical treatment. The intervention is performed in the first 24 - 48 hours, and in those who are not operated on within that period, high percentages of complications occur. In-hospital mortality was low.